Historisitas Perkembangan Ilmu Pengetahuan dan Filsafat Ilmu dalam Perspektif Sejarah - Shabrina Azzah Nabilah; Ifahuryati; Ahmad Nazmi Rafi Akbar; Muhammad Naufal Gustianoputra; Bima Prima Panggayuh (Yayasan Al-Afif, 2026)
The development of science is a historical process shaped by social, cultural, political, and intellectual changes, making it essential to understand this trajectory in relation to human civilization. This study aims to examine the historical development of science and philosophy of science from the classical era to the modern period and their relevance to civilizational progress. A qualitative descriptive approach was employed using the library research method, analyzing relevant literature such as books, scientific journals, and academic documents. The findings show that science began with rational thinking traditions in Ancient Greece, advanced significantly during the Islamic Golden Age through the integration of revelation, reason, and empirical experience, and continued evolving through the Renaissance and modern era via the scientific method and philosophical schools like rationalism, empiricism, criticism, and positivism. Consequently, philosophy of science plays a vital role in shaping ethical, moral, and humanitarian foundations for scientific and technological progress.